Accounting Conservatism: Growth, Ownership, Distress, and Governance Interaction - Amanda Hermannisa; Badingatus Solikhah (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2026)
This study examines the relationship between accounting conservatism in Indonesian non-financial firms and growth opportunity, managerial ownership, and financial distress, addressing conflicting findings in prior research and governance differences. Good Corporate Governance is used as a moderating mechanism to understand its effect on financial reporting. Using 8,440 firm-year observations from companies listed on the Indonesia Stock Exchange from 2015 to 2024, accounting conservatism is measured by the difference between net income and operating cash flow. Panel regression models assess direct effects and the moderating role of GCG, represented by board size and independent directors. Data from Refinitiv are analyzed through regression, correlation, descriptive statistics, and interaction terms. Results indicate growth opportunity, managerial ownership, and financial distress positively affect accounting conservatism. GCG moderates these relationships: independent members reduce the effect of financial distress, while larger boards and more independent members strengthen managerial ownership impact and weaken that of growth opportunity.